2017
DOI: 10.5114/cipp.2017.66092
|View full text |Cite
|
Sign up to set email alerts
|

Parentification – its direction and perceived benefits in terms of connections with late adolescents’ emotional regulation in the situation of marital conflict

Abstract: <b>Background</b><br /> Parentification means distortion of the roles between family members. A child performs adult tasks and responsibilities for his siblings and/or parents. The aim of the study was to extend the knowledge about parentification and its connections with parental conflict as well as strategies of coping with parental conflict in the group of late adolescents who live with their parents or live on their own.<br /> <br /> <b>Participants and procedure</b&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The study had a novel goal to explore the relation between resiliency and parentification in the sample of Polish adolescents for the first time. It is important to explore the parentification process in the group of Polish adolescents because so far, most of the Polish studies on parentification concerned adults or emerging adults, and those studies were retrospective [ 23 , 24 , 32 , 36 ]. Moreover, a former nationwide study conducted among Polish adolescents aged 11–17 showed that 72% of the respondents experienced at least one form of abuse or neglect [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study had a novel goal to explore the relation between resiliency and parentification in the sample of Polish adolescents for the first time. It is important to explore the parentification process in the group of Polish adolescents because so far, most of the Polish studies on parentification concerned adults or emerging adults, and those studies were retrospective [ 23 , 24 , 32 , 36 ]. Moreover, a former nationwide study conducted among Polish adolescents aged 11–17 showed that 72% of the respondents experienced at least one form of abuse or neglect [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The earlier a child experienced a disruption in the family’s hierarchy and the longer it lasted, and also the more often the child performed age-inappropriate tasks inadequate in terms of its capabilities, the more severe were the consequences of parentification [ 15 , 20 , 31 ]. The emergence of obligations towards the family at an older age, short-lasting burdens, and performing tasks coherent with cultural norms might have worked in favor of perceiving the situation as less stressful and more just by the child [ 17 , 20 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter pertains to the child being available to all the family's emotional needs. However, the child's emotional needs are not addressed as they serve as the emotional pillar of the family (Stevens, 2015;Borchet & Lewandowska-Walter, 2017;Owsley, 2019). In contrast, instrumental parentification refers to the child taking care of the living conditions of the family unit such as the upkeep of the house itself (Bobis et al, 2018).…”
Section: Parentification Experiences (Definition Types and Domains)mentioning
confidence: 99%
“…Instrumental parentification occurs when children are assigned to perform functional duties such as household chores (e.g., cooking or cleaning) and handling finances (e.g., paying household bills). It is more practical than emotional parentification, wherein children must provide emotional support to parents without expecting reciprocation (Stevens, 2015;Borchet & Lewandowska-Walter, 2017). Research has suggested that parentification impacts the child differently depending on their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In this pattern of family interactions, the child (also as an adult) provides care and support towards his/ her parent instead of receiving it from the parent (Jurkovic, 1997;Hooper, Marotta & Lanthier, 2008;Hooper, DeCoster, White, & Voltz, 2011;Schier, 2010Schier, , 2014. The phenomenon of parentification appears when, due to a family system disadvantageous for the child, the child must shoulder a burden of responsibilities, so that he/she is unable to entirely engage into his/her own developmental tasks (Jurkovic, 1997;Hooper, 2007;Schier, 2010;Rostowska & Borchet, 2016;Borchet & Lewandowska-Walter, 2017). Research on young adults indicates various outcomes of parentification.…”
Section: Introductionmentioning
confidence: 99%